Crónicas coloniales - Fernández Guardia, Ricardo (San José CR: Editorial Costa Tica, 1967)
Trata importantes pasajes históricos de la Costa Rica colonial.
Keywords: COSTA RICA; HISTORIA COLONIAL; COLONIAS